2002
DOI: 10.1038/sj.onc.1205979
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of primary non-small cell lung cancer for target identification

Abstract: Using a panel of cDNA microarrays comprising 47 650 transcript elements, we have carried out a dual-channel analysis of gene expression in 39 resected primary human non-small cell lung tumours versus normal lung tissue. Whilst *11 000 elements were scored as differentially expressed at least twofold in at least one sample, 96 transcripts were scored as over-represented fourfold or more in at least seven out of 39 tumours and 30 sequences 16-fold in at least two out of 39 tumours, including 24 transcripts in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
114
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(127 citation statements)
references
References 27 publications
(25 reference statements)
11
114
1
1
Order By: Relevance
“…Whether the degrading enzyme, 15-PGDH, plays any role in contributing to the elevated levels of PGE 2 in tumors is not clear. Heighway et al (10) reported that 15-PGDH was under-represented at least 2-fold in 69% of lung tumor in a cDNA microarray study. Ding et al (11) also showed that 100% of lung tumor-tissue pairs exhibited a 2-fold decrease in 15-PGDH expression and 61% exhibited a 10-fold decrease using quantitative RT-PCR analysis.…”
Section: Down Regulation Of 15-pgdh Expression In Lung and Other Tumorsmentioning
confidence: 99%
“…Whether the degrading enzyme, 15-PGDH, plays any role in contributing to the elevated levels of PGE 2 in tumors is not clear. Heighway et al (10) reported that 15-PGDH was under-represented at least 2-fold in 69% of lung tumor in a cDNA microarray study. Ding et al (11) also showed that 100% of lung tumor-tissue pairs exhibited a 2-fold decrease in 15-PGDH expression and 61% exhibited a 10-fold decrease using quantitative RT-PCR analysis.…”
Section: Down Regulation Of 15-pgdh Expression In Lung and Other Tumorsmentioning
confidence: 99%
“…Comparative multiplex (cm) RT -PCR was used to compare levels of test gene transcripts between normal lung and tumour samples, as described previously (Heighway et al, 2002;Smith et al, 2003). Briefly, the test gene transcript was coamplified with a nondifferentially expressed control transcript (APPBP2 -KIAA0228) in the same reaction.…”
Section: Comparative Multiplex Rt -Pcrmentioning
confidence: 99%
“…Levels of S100A2 transcript in tumour samples of this new series were compared to those in matched normal lung, by cmRT -PCR. An endogenous control transcript (ABPPBP2) previously identified as not differentially expressed between normal lung and lung tumours (Heighway et al, 2002) was used as an internal control transcript. Results of this analysis are illustrated in Figure 1.…”
Section: S100a2 Expression In Nsclcmentioning
confidence: 99%
See 2 more Smart Citations